Biodegradation potential of polycyclic aromatic hydrocarbons by bacteria strains enriched from Yangtze River sediments. Issue 5 (3rd March 2016) - Xu, Xiaoyi; Chen, Xi; Su, Pan; Fang, Fang; Hu, Bibo
ABSTRACT: Microbial degradation is an effective method for the removal of polycyclic aromatic hydrocarbons (PAHs) compounds from polluted sediments. Surface sediments collected from Yangtze River in the downtown area of Chongqing were found to contain PAH concentrations to various different degrees. Two bacteria strains (termed PJ1 and PJ2) isolated from the sediment samples could use phenanthrene (Phe) and fluoranthene (Flu) as carbon sources for growth thereby degrading these two PAH compounds. Using 16S rDNA gene sequencing, the isolates were identified as Sphingomonas sp. and Klebsiella sp., respectively. Biodegradation assays showed that the PJ1 presented an efficient degradation capability compared to PJ2 in cultures with the initial Phe and Flu concentrations ranging from 20 to 200 mg/L. The highest rates of Phe and Flu biodegradation by PJ1 reached 74.32% and 58.18% after incubation for 15 and 30 days, respectively. This is the first report on the biodegradation potential of the bacterial from surface sediments of an industrial area upstream of the Gorge Reservoir.